2023
DOI: 10.3389/fpubh.2023.1062325
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health service use and associated factors among youths in Becho district, southwest Ethiopia

Abstract: BackgroundYoung people are less informed, less experienced, and less at ease when it comes to accessing reproductive health services than adults. Though youth-friendly services are designed to accommodate the unique needs of youth, in developing countries like Ethiopia, studies on the level of utilization of reproductive health services are limited.ObjectivesThis study determined the level of reproductive health (RH) service use and associated factors among youths.MethodsA community-based cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The findings from this study emphasize the crucial of using a two-level random slope model to model the determinant of RHS utilization among Assosa University regular class students. In line with previous study, this study revealed that the covariates; student’s awareness about RHS, gender, preference of service fees and student’s monthly average income were significant predictor variables of RHS utilization [ 8 , 30 – 32 ]. In this study findings, students who; preferred service fee as usual rate, have awareness about RHS, are females and have high monthly average income were more likely to utilize RHS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings from this study emphasize the crucial of using a two-level random slope model to model the determinant of RHS utilization among Assosa University regular class students. In line with previous study, this study revealed that the covariates; student’s awareness about RHS, gender, preference of service fees and student’s monthly average income were significant predictor variables of RHS utilization [ 8 , 30 – 32 ]. In this study findings, students who; preferred service fee as usual rate, have awareness about RHS, are females and have high monthly average income were more likely to utilize RHS.…”
Section: Discussionsupporting
confidence: 89%
“…Indirectly, this findings support the findings of present study in the way that students with high monthly average income are more likely to have access to RHS and to be afford of the cost for these services. According to [ 30 – 32 , 38 ] study findings, students who were aware of RHS were more likely than those who were not to make use of these services. This is also another consistent result from the present study finding.…”
Section: Discussionmentioning
confidence: 99%
“…This creates large gaps in knowledge across multiple generations because experiences are not passed down through the family line ( 40 , 66 ). To foster responsiveness among adolescents, it is overbearing to embrace change and establish consensus within families regarding the open discussion of SRH issues ( 67 ). Thus, bridging the gap within the family on SRH issues will improve the sustainability of positive changes and the transmission of accumulated experiences.…”
Section: Discussionmentioning
confidence: 99%